2019
DOI: 10.5194/isprs-annals-iv-2-w5-503-2019
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Landslide Susceptibility Mapping Using Remote Sensing Data and Machine Learning Algorithms in Iran

Abstract: <p><strong>Abstract.</strong> Landslide is painstaking as one of the most prevalent and devastating forms of mass movement that affects man and his environment. The specific objective of this research paper is to investigate the application and performances of some selected machine learning algorithms (MLA) in landslide susceptibility mapping, in Dodangeh watershed, Iran. A 112 sample point of the past landslide, occurrence or inventory data was generated from the existing and field observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Moreover, there were strong correlation between profile curvature and curvature, and curvature and plan curvature with a value of 0.82 and 0.80, respectively. In this case, the simple method to overcome with high Pearson correlation between conditioning factor is to remove one of the factors from the dataset and rebuild analtysis 1 . On the other hand, factor optimization using Chi-Square indicated that higher Chi-square values with p-value less than 0.05 ranks the significance of each factor for landslide prediction.…”
Section: Factor Analysis and Optimization Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there were strong correlation between profile curvature and curvature, and curvature and plan curvature with a value of 0.82 and 0.80, respectively. In this case, the simple method to overcome with high Pearson correlation between conditioning factor is to remove one of the factors from the dataset and rebuild analtysis 1 . On the other hand, factor optimization using Chi-Square indicated that higher Chi-square values with p-value less than 0.05 ranks the significance of each factor for landslide prediction.…”
Section: Factor Analysis and Optimization Resultsmentioning
confidence: 99%
“…Whereas, TRI indicates the variation in the elevation of neighboring cells in a digital elevation cells network. We classified the SPI, TWI, TRI (Figure 1h,i,j) based on 5 classes as per reference 1 , which further definitions are available there.…”
Section: Stream Power Index (Spi) Topographic Wetness Index (Twi) Terrain Roughness Index (Tri)mentioning
confidence: 99%
See 1 more Smart Citation
“…The rules are worked out based on the structure of the data. The tree starts with a highly influential attribute as the root node and successive rules are applied to move to the next attributes until a leaf node or terminal node is reached [60,61]. The data set is split repeatedly from the coarsest attributes to the finest attributes.…”
Section: Pairwise Analysis Of Parametersmentioning
confidence: 99%